If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 = 4x + 6 Reorder the terms: 12 = 6 + 4x Solving 12 = 6 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 12 + -4x = 6 + 4x + -4x Combine like terms: 4x + -4x = 0 12 + -4x = 6 + 0 12 + -4x = 6 Add '-12' to each side of the equation. 12 + -12 + -4x = 6 + -12 Combine like terms: 12 + -12 = 0 0 + -4x = 6 + -12 -4x = 6 + -12 Combine like terms: 6 + -12 = -6 -4x = -6 Divide each side by '-4'. x = 1.5 Simplifying x = 1.5
| L=-9c+4b-8b+6c-3c+6b | | 9y-5=0 | | 10+2(2x-1)=16 | | (ln^2x)=4x | | (lnx^2)=4x | | 2x^2-60x=2x^2 | | W=-5c+3c-9+4 | | z+3(2-i)=5+i | | S=-5b-3b+6-7 | | x^2+x+2.5=0 | | D=-9c+6c-8c | | 64/x=4 | | A=-7y+6y | | 0.50x+0.25(30)=21.5 | | 50+(6x-2)=180 | | B=-9x-3x | | -14(2x-10)=28 | | 4a-3=15 | | 5x+5=8x-9 | | -5p+5+6p=10 | | Ep+q=29 | | f(x+3)=x^2+5x+3 | | M=-4x+9z-9+2x-2z+4 | | 2(x-5)=3(5x+1) | | 9x-4=52-5x | | x^4-3x^3+4x+1=0 | | B=6x+3a-9+7x-8a+2 | | 4x-7+9x+13-5x-4= | | 6*x+x=63 | | 27=y-11 | | 3/(1-sqr19) | | 7x+17x+3y=180 |